Makna Lagu Himawari Karya Kawasaki Futoshi Dan Akimoto Yasushi - Trisna Windasari, Putu; Rauh Artana, I Nyoman; Damayanti, Silvia (Humanis, 2016)
This research describes the meanings and message contained in the Himawari songs by Kawasaki Futoshi and Akimoto Yasushi. The data analyzed using descriptive analysis method. This research used the theory of semiotics by Riffaterre (1978) and the theory of moral by Nurgiyantoro (1995). Based on the analysis, the meaning of Himawari song by Kawasaki Futoshi are indicates the spirit to endure our life. Meanwhile, the meaning of Himawari song by Akimoto Yasushi are indicates the hopes that had grown in ourselves and the struggle to achieve a bright future. The messages contained in both Himawari lyrics are divided into two, namely:  explicit and implicit.